Tantangan Hukum Keluarga Islam dalam Sistem Pendidikan Kontemporer: Perspektif, Konflik, dan Solusi - Ubaidilah, Asep (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2024)
This article discusses the challenges faced by Islamic law in the contemporary education system, focusing on perspectives, conflicts, and solutions. The developments in globalization and technology have transformed the educational landscape, creating the need to integrate Islamic law values into an increasingly secular curriculum. This article identifies several key issues, including differing interpretations of Islamic law, a lack of understanding among educators, and the marginalization of important elements of Islamic law. Conflicts often arise regarding curriculum, teaching methods, and educational policies. To address these challenges, this article offers solutions that include adaptive and innovative Islamic education approaches, as well as the integration of fundamental principles of Islamic law with modern educational methods and technologies. This research aims to bridge the gap between Islamic law and the contemporary education system, ensuring the relevance and positive contribution of Islamic law in shaping an educated and morally upright generation.